Portfolio optimization and valuation capability of multi-factor models: an observational evidence from Dhaka stock exchange - Kabir, Md. Ahsan; Liping, Yu; Sarker, Sanjoy Kumar; Nahiduzzaman, Md.; Borman, Tanmay (Frontiers in Applied Mathematics and Statistics, 2023)
The main goal of this study is to examine the return explanation strengths of the Carhart fourfactor, the Fama-French three-factor, and the single-factor models in the context of the Bangladeshi stock market. We, therefore, reveal the risk-adjusted returns, test the valuation capability of multifactor models, and estimate optimal portfolio weights of stocks listed in DSE under the DSE30 index. Our findings demonstrate that large capitalization firms that have low or medium book-tomarket (B/M) ratios produce more concentrated returns than their counterparts, resulting in greater earnings per unit of total, systematic, and downside risks. Furthermore, we discover that each factorial value has an impressive capacity to explain the market excess returns, however, the influence of factor values on the cross-section of stock returns is somewhat contradictory. In particular, the momentum factor is unable to describe the cross-section excess returns, whereas the risk premium, size, and value factors have a significant impact on the cross-section excess returns. Finally, we find that a Large-cap firm with a low B/M ratio is suitable for risk-seeking investors, in contrast, a small-cap firm with a low B/M ratio is appropriate for lower-risk tolerance investors. Moreover, our empirical outcomes have noteworthy implications for private companies, investors, and policymakers.